PENGARUH KUALITAS PELAYANAN ADMINISTRASI KEUANGAN TERHADAP TINGKAT KEPUASAN MAHASISWA DI UNIVERSITAS BANTEN JAYA - Elsa Amalia; Budi Mulyati; Fitri Nurlaili (FKIP, Universitas Banten Jaya, 2023)
This study aimed to determine the effect of the quality of financial administration services on student satisfaction at the Banten Jaya University. This research was a quantitative research. The population of this study was active students of Banten Jaya University in 2022 and the sample of this study used a simple random sample with a total sample of 95 students. The type of data was primary data. The data analysis technique used classical assumption test and simple linear regression analysis, T-test and coefficient of determination. The results that the value of tcount (8.876) > ttable (2.638), it was indicated that the quality of financial administration services had positive effect on student satisfaction. The coefficient of determination was 46%. It could be said that there was an influence of the service quality on the student satisfaction at Banten Jaya University.